Off Detailed Balance: Non-Equilibrium Steady States in Catalysis, Molecular Motors and Supramolecular Materials - Goldup, Stephen; Aprahamian, Ivan (ChemRxiv)
All chemists are familiar with the idea that, at equilibrium steady state, the relative concentrations of species present in a system are predicted by the corresponding equilibrium constants, which are in turn related to the relative free energy difference of the system components. There is also no net flux between species, no matter how complicated the reaction network. Achieving and harnessing non-equilibrium steady states, by coupling a reaction network to a second spontaneous chemical process, has been the subject of work in a number of disciplines including the autonomous operation of molecular motors, the assembly of supramolecular materials, and strategies in enantioselective catalysis. Here we juxtapose these linked fields to highlight their common features, the similar issues that must be overcome, and some common misconceptions that may be serving to stymie progress.